Enhancing Brick Production Efficiency through the Implementation of Lean Manufacturing using the Waste Assessment Model (WAM) - Fitriadi Fitriadi; Efriansyah Efriansyah; Muhammad Firdaus (Journal Of Management Analytical and Solution (JoMAS), 2026)
Competition in the manufacturing sector requires companies of all sizes tomaintain efficient production performance and eliminate waste. LeanManufacturing serves as a strategic approach to minimize waste and enhanceprocess efficiency. UD Surya, a small-scale enterprise producing concrete bricks,faces various challenges related to production capacity and effectiveness,particularly involving wastes such as overproduction, defects, inventory,processing, waiting, transportation, and motion. This study aims to improve theefficiency of brick production through the implementation of LeanManufacturing using the Waste Assessment Model (WAM). The WAM methodis employed to quantitatively identify waste levels, supported by Pareto diagramanalysis to determine priority issues. The results indicate that several categoriesof waste exceed the 15% threshold, requiring immediate corrective actions toprevent further losses and improve production efficiency. These findingsdemonstrate that the application of Lean Manufacturing based on WAM iseffective in identifying critical waste and provides a strong foundation forcontinuous improvement strategies in the brick production process at UD Surya.